A multidisciplinary study of Iberian Chalcolithic dogs - Blaschikoff, Ludmilla (2022)
Domesticated dogs have been present in the Iberian Peninsula long before other domesticated species, back to the late Palaeolithic period. Their origin is still uncertain, but dogs were already well established during the Chalcolithic period (ca. 5000-4000 BP). This study employed a multidisciplinary approach comprising osteometric, radiographic and palaeogenomic analyses to characterize Chalcolithic Iberian Canis remains. Two Chalcolithic archaeological sites - Leceia, Oeiras, in Portugal, and El Caset ' on de la Era, Villalba de los Alcores, Valladolid, in Spain - were the main focus of this study. Osteometric and odontometric data from eleven other sites in Iberia were also included. Osteometric results show signs of phenotypic variability, likely the result of human-driven selective pressure. Dental radiographic and dental wear analyses allowed age at death estimation for four individuals (two juvenile and two adults). Three Chalcolithic Iberian dogs had their mitogenomes resequenced and the mitochondrial DNA analysis allowed to assign each individual to two of the major known haplogroups - A and C. Molecular sex infered by the chromosomeX/chromosome1 coverage ratio allowed to identify one female and two males. This study unveils some aspects of the Iberian Chalcolithic dogs: these dogs already exhibited various morphotypes whose profiles might be associated to the performance of certain tasks, as well as mitogenomes of two distinct lineages that help tracking the evolutionary paths of Iberian dogs.